2021
DOI: 10.36909/jer.10841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of several patterns of floating stone columns on the bearing capacity and porewater pressure in saturated soft soil

Abstract: One of the common geotechnical problems is the construction on soft soil and the improvement of its geotechnical properties to meet the design requirements. A stone column is one of the well-known techniques used to improve the geotechnical properties of soft soils. Sometimes thick layers of soft soil imposed the designer to use floating stone columns for improvement of such soil; in this case, the designer will be lost the end bearing of the stone column. In this study, the effects of several patterns of floa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As previously stated, the end-bearing columns have higher n values than the floating columns, aside from the most significant finding: this procedure is highly effective in fragile soils. At the same time, the results of the experiments showed that floating stone columns could be used to improve the ultimate bearing capacity of soft soil despite the modest area replacement ratio [21][22][23][24]. An elastic modulus ratio (Ec/Es), which indicates a stone column's elastic modulus, is shown in Figure 6 as a function of the stress concentration ratio, n. The stiffness ratio affects the stress concentration ratio, particularly in the end-bearing columns.…”
Section: Resultsmentioning
confidence: 94%
“…As previously stated, the end-bearing columns have higher n values than the floating columns, aside from the most significant finding: this procedure is highly effective in fragile soils. At the same time, the results of the experiments showed that floating stone columns could be used to improve the ultimate bearing capacity of soft soil despite the modest area replacement ratio [21][22][23][24]. An elastic modulus ratio (Ec/Es), which indicates a stone column's elastic modulus, is shown in Figure 6 as a function of the stress concentration ratio, n. The stiffness ratio affects the stress concentration ratio, particularly in the end-bearing columns.…”
Section: Resultsmentioning
confidence: 94%
“…Figure 8 refers to an increment of about 112% PWP when the river level rises from (0 to 7) m above the trench slope base. This leads to a slope settlement increase from 21 to 69 mm and a decrease in shear resistance and stability of the trench slope materials [12][13][14][15][16][17][18][19][20][21][22]. So, the values of FS reduced to (0.846) when the level of Tigris River elevation was 7 m above the trench slope base, as explained in Figure 9.…”
Section: Effect Of Increased Pore Water Pressure On Castle Stabilitymentioning
confidence: 99%
“…He also noted that the use of the square pattern is more effective. of the square distribution even though they have the same area substitution ratio (22). In this study, the stone columns covered with a comprehensive cover with a length of 1.5 meters and a diameter of 15 cm were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The encasement, which has several advantages, further restrains the stone column. increased column stiffness, prevention of stone loss into the soft clay around it, and preservation of the drainage and frictional properties of the stone aggregates (20)(21)(22). The bearing capacity and porosity pressure are influenced by the distribution of various types of stone columns.…”
Section: Introductionmentioning
confidence: 99%